Państwowa Komisja Wyborcza A.D. 2026 – jaki centralny organ wyborczy (nie)powinien być? - Nawrot, Oktawian; Lemańska, Joanna (PRAWO i WIĘŹ, 2026)
The article examines whether the current institutional model and practical functioning of the National Electoral Commission (PKW) comply with European standards concerning central electoral bodies, and whether the Commission is capable of ensuring voters’ trust in the integrity of the electoral process. The authors reconstruct the relevant standards developed by the Venice Commission and ODIHR regarding the operation of central electoral bodies, with particular emphasis on the principle of neutrality of the “rules of the game”, the need to ensure balanced political representation within election-managing bodies, and the independence, impartiality, and professionalism of their members. In this context, the analysis focuses on the 2018 amendment to the Electoral Code, which transformed the PKW from a judicial type body into a mixed commission largely appointed by the Sejm, as well as on the functioning of the PKW in its current composition. The authors identify a number of systemic deficiencies, including violations of the principle of proportional representation of parliamentary forces, a low level of gender balance, limited representation of desirable subject-matter expertise, and controversial decisions concerning the financing of the main opposition party – criticized both in court rulings and in ODIHR reports. The authors argue that although the model of a multiparty commission is not, in itself, incompatible with European standards, the way the PKW operates significantly undermines the desired neutrality and credibility of this body and, consequently, weakens citizens’ trust in the democratic electoral process.